Cross-metathesis of unsaturated natural oils with 2-butene. High conversion and productive catalyst turnovers - Elaridi, Jomana (2005)
The cross-metathesis of synthetic and natural triglycerides containing unsaturated fatty acids with 2-butene can be achieved with high conversion and excellent productive turnovers. These reactions are catalysed by second-generation ruthenium-based olefin metathesis catalysts and can be conducted at −5 °C in liquid 2-butene.